Clinicoepidemiological Profile and Prognostic Factors in Neurotuberculosis in Children - Vikas Sharma; Krishnan Rajeshwari; Deepak Kumar; Garima Gupta (Korean Child Neurology Society, 2023)
Purpose This study aimed to determine the clinicoepidemiological profile and prognostic factors in children with neurotuberculosis. Methods An observational study was conducted at a tertiary care hospital on 50 children diagnosed with neurotuberculosis. The demographic profile, clinical details, and all investigations were recorded on a predetermined form and datasheet for analysis, and disability severity was graded using the modified Rankin Scale. Results Fifty patients were enrolled (male-to-female ratio, 1.08:1). Younger children (1 to 3 years) were more commonly affected. Most patients were malnourished, and only 58% had been immunized with the Bacillus Calmette-Guerin vaccine. Fever was the most common symptom (96%) followed by headache, altered consciousness, vomiting, seizures, and abnormal posture. On cerebrospinal fluid (CSF) analysis, 87% of patients showed pleocytosis with lymphocytic predominance. More than 80% of patients had CSF protein levels >100 mg/dL and CSF glucose levels <60 mg/dL. Common findings on neuroimaging were hydrocephalus (76%), basal meningeal enhancement (60%), basal exudates (52%), and parenchymal infarcts (32%). We noted a mortality rate of 40%, of whom 87.5% had modified British Medical Research Council (BMRC) stage 3 tubercular meningitis (TBM). All patients who survived stage 3 TBM had a severe disability, and over 50% of patients with stage 2 TBM had moderate to severe disabilities. Conclusion Young age, lower socioeconomic status, BMRC stages 2 and 3, abnormal posture, hydrocephalus, and the presence of basal exudates were associated with poor outcomes. High suspicion is needed for early diagnosis and prevention of disability and mortality.